Pengaruh Pemberian Motivasi Dalam Bentuk Service Charge Terhadap Peningkatan Prestasi Kerja Karyawan (Studi Kasus Pada Fave Hotel A. Yani Banjarmasin) - Mursanto Mursanto; Meira Meira (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to determine the effect of providing a service charge on employee performance at Fave Hotel A. Yani Banjarmasin. This research is a type of quantitative approach research, in this study the population to be studied were all employees of Fave Hotel A. Yani Banjarmasin totaling 72 people. The way to determine the number of samples in this study is by saturated sampling. Data analysis techniques using validity test, reliability test and hypothesis testing. Providing incentives to employees at Fave Hotel Banjarmasin seen from the partial t test proves that t count 3.310 > t table 1.66691 or a significant level of 0.001 <0.05, which means that the incentive variable (X) partially has a significant effect on work performance at Fave Hotel Banjarmasin . This means that the first hypothesis is accepted. The provision of incentives to employees at Fave Hotel Banjarmasin seen from the f test simultaneously proves that the probability value is less than 0.05, which means that employee incentives through service charges greatly affect employee performance. This means that the second hypothesis is accepted. Based on the coefficient of determination, the Adjusted R Square value is 0.898, which means that 89.8 percent of employee performance variables can be explained by the independent variable, namely service charge and the remaining 11.2 percent is influenced by other factors not present in the study.